Measuring Food Insecurity in Wollongong - Mohd Abu Bakar, Wan Azdie; Yeatman, Heather; Condon-Paoloni, Deanne (Karger, Switzerland, 2009)
This study aim to establish a standard assessment measure of the extend of food insecurity in Australian communities.